Prosthetic Techniques to Increase the Accuracy of Scan Bodies and Influential Factors: A Systematic Review - Sayed Shojaodin Shayegh; Maryam Jahangiri (Journal of Mashhad Dental School)
Background: Intraoral scanning is used in digital impression taking. Scan bodies are used for three-dimensional implant scanning. These parts help to accurately transfer the position, location and angle of the implants to the laboratory technician. Each scan body consists of three parts: the base, body and scannable surface. The scannable surface is available in different shapes, sizes and materials. This study aimed to evaluate the various factors affecting the accuracy of scan bodies and to also determine the prosthetic techniques that would enhance the accuracy of digital impressions taken from edentulous jaws.Methods and Materials: This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. A comprehensive search was conducted across databases such as PubMed, Scopus and Google Scholar using terms related to “CAD/CAM”, “implant impression”, “edentulous”, “dental implants” and “oral rehabilitation”.  Studies that were published from January 2015-Feburary 2024, in English language, were retrieved.Results: A total of 295 studies were initially identified and 49 articles were screened by title and abstract. After eliminating studies that were irrelevant to our PICO model, the full text of 23 article were reviewed. Scan bodies are categorized as either clinical or laboratory. The following factors were identified as influential factors affecting the accuracy of scan bodies: height, diameter, geometric shape, placement angle, torque, and material.Conclusion: This study showed that some prosthetic methods can be employed to increase the accuracy of the final digital impression taken in edentulous jaws. These methods include using the continuous bar strategy, modified scan bodies or reverse scan bodies.